Redox metabolism in mussels (Brachidontes solisianus) under the influence of tides in a rocky beach in Southern Brazil. (5th September 2021) - Moreira, Daniel C.; Sabino, Marcus A.C.T.; Kuzniewski, Felipe T.B.; Furtado-Filho, Orlando V.; Carvajalino-Fernández, Juan M.; Angelini, Ronaldo; Freire, Carolina A.; Hermes-Lima, Marcelo
Abstract: Aquatic invertebrates use antioxidant systems to endure intertidal environments, where temperature, oxygen availability and radiation incidence vary greatly. The upregulation of antioxidants during oxygen-limiting conditions, such as intertidal aerial exposure (AE), is known as preparation for oxidative stress (POS). Preparation for oxidative stress has been commonly reported for animals exposed to hypoxia in the lab, but few studies have investigated it under ecologically relevant natural settings. Here, we studied metabolic enzymes, antioxidants, and oxidative stress markers in Brachidontes solisianus mussels exposed to a natural tidal cycle in a rocky beach in Southern Brazil. Animals were collected at 6 time-points throughout the tidal cycle: after 2 h of AE; then after 1 h, 3 h, and 7 h of immersion; followed by 0.5 h and 4 h of AE. The activities of malate dehydrogenase, isocitrate dehydrogenase, and pyruvate kinase were unaffected by aerial exposure. Similarly, the acitivities of enzymes of the antioxidant system, catalase, glutathione transferase, glutathione reductase, and glucose 6-phosphate dehydrogenase did not change significantly throughout the tidal cycle. In contrast, total and reduced glutathione levels significantly increased at 4 h AE by 47% and 64%, respectively, compared with those in submerged mussels (1 h, 3 h, and 7 h immersion groups combined). Lipid peroxidation and carbonyl protein levels significantly increased after 4 h of AE compared with those in mussels underwater for 7 h. Our results indicate the occurrence of POS in B. solisianus mussels exposed to air under natural conditions during tidal cycles. Graphical abstract: Image 1 Highlights: B. solisianus suffers oxidative stress after air exposure (4 h) in natural conditions. Air exposure elicited increases in total (47%) and reduced glutathione (64%) levels. No changes were observed in the activity of metabolic and antioxidant enzymes. Results indicate the occurrence of "preparation for oxidative stress" in the wild.